Experiences of Nursing Students Working with Nurses during Clinical Practice - Šulskytė, Justė; Spirgienė, Lina (Slauga. Mokslas ir praktika, 2024)
The aim of the study: to establish nursing students’ experiences of working as a team with nurses during clinical practice. Methods. The qualitative research was carried out between December 2023 and February 2024. 9 female students of the 4th year nursing programme at LSMU were interviewed. Approval for the study was obtained from the LSMU Bioethics Center (No. 2023-BEC2-396, 14 November 2023). Research results. Professional nurses were the key individuals who taught how to perform procedures, communicate with patients, encouraged professional improvement, and provided emotional support in difficult and stressful situations. The participants were pleased when the involved nurses were paying due attention to the process of training and showed the trainees from their own experience how to carry out procedures more effectively. The students positively commented on the nurses’ ability to teach students. According to the research participants, if the students themselves show initiative, nurses willingly involve them in critical situations. By motivating students, nurses can create a stronger bond with them, and, most importantly, encourage them to never give up, and to have more confidence in their own abilities. The experiences of nursing students depended on the course in which they were carrying out their clinical practice. Conclusions. Experiences in the clinical practice influence nursing students’ perceptions of the nursing profession and teamwork. Nursing students stated that they mostly worked in teams with nurses, learning by observing their actions and later trying out their own abilities in various nursing procedures.